Collection of approaches to conduct food system assessments in local settings - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Methodlogy for food flow assessment was developed and piloted in Ethiopia by Msc students of Wageningen University. Rural-urban transect food system assessment finalized and briefs developed. Compendium of indicators finalized and will be published in 2020; country briefs piloted and finalized in 2020. Included in food system trainings.